HUBUNGAN ANTARA KARAKTERISTIK PERUSAHAAN DENGAN IMPLIED COST OF CAPITAL PADA PERUSAHAAN DI INDONESIA - Bahtiar Usman (Universitas Trisakti, 2003)
This study, proposes an altenative technique for estimating the cost of capital. Specifically, it use discounted residualincome model. The examine firms characteristic that are systemati- cally related to this estimate of cost of capital, it show that a firm's cost of capital isa function of its long term Debt to Book Ratio (Ln D/B), Long Fim Size (Ln Size), Eaming Variability (Ln Ev) and Long Debt to Market Ratio (Ln D/M). These variables explain around 63% of the coss secional variaton in future implied costof capital. The findings suggest that they can be exploited to estimate future cost of capital in Indonesia.